The role of the Internet in open innovations models development - Jelonek, Dorota (Rola internetu w rozwoju modeli innowacji otwartych, 2012)
This paper analyses the new open innovations models: value co-creation model, co-creation experience innovation, user-driven innovation model and crowdsourcing. The chosen internet services which support communication and cooperation between companies and consumers and consumers communities were presented. The aim of the paper is to show that the presented open innovation models are benefiting from the evolution of new alternatives of networking collaboration
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 1 (23), s. 38-47
Keywords: open innovation model; co-creation model; co-creation experience innovation; user-driven innovation model; model innowacji otwartych; model współtworzenia wartości; model współtworzenia innowacji na bazie doświadczeń; Internet